A Analisis Gender Based Violence dalam Konvensi CEDAW Pada Isu Kekerasan Seksual di Korea Selatan - Kardina, Kardina (Jurnal Ilmu Hubungan Internasional LINO, 2021)
This research describes about the implementation of CEDAW on Gender-Based Violence in South Korea which is a common issue with the target victim is female. The perspective used in this study is Radical Feminism with the concept of Compliance and Gender-Based Violence. This problem occurs because of two factors, namely patriarchal culture and economic factors. Confucianism is the basis for the formation of a patriarchal culture with the essence of teachings that lead to discrimination against women, in addition to the factors of economic inequality that also trigger an increase in violence. Thus the results of the study showed that South Korea is experiencing the barriers are significant enough to implement CEDAW although it has ratified it since 1984. Keywords: South Korea; Gender Based Violence; Confucianism; Patriarchal Culture; CEDAW